Pola Komunikasi Lintas Budaya Indonesia-Turki Pada Platform Ankaranesia - Esmeralda Vidi Leodafira; Riesta Ayu Oktarina (DIGICOM : Jurnal Komunikasi dan Media, 2022)
The research focuses on the pattern of Indonesian-Turkish cross-cultural communication and the supporting and inhibiting factors in interpersonal communication on the Platform AnkaranesiaThis research is to find out what patterns and factors are the interest of Indonesian students in learning a Turkish language and culture. This type of research is descriptive qualitative because it studies about social behavior, interpersonal communication on Indonesian students in cross-cultural communication. Using a case study approach because it is identical to researching a process. The process in question is an overview of the process of Indonesian students in learning the Turkish language and culture. Qualitative research can describe in depth and detail through the phenomena that have been selected by the researcher. The analysis technique in this study uses the model of Matthew B. Miles and A. Michael Huberman. Primary data taken through the process of observation, in-depth interviews, and documentation. Theories used in this research are communication patterns, cross-cultural communication, interpersonal communication, Ankaranesian students' social behavior in communication, and behavioristic theory. The results showed that the pattern of cross-cultural communication in Indonesian students could show development in interacting using the Turkish language and promote good impact in social relations. Then the supporting and inhibiting factors that occur can be resolved because of actions in unifying thoughts, and communication becomes the main key for the Platform Ankaranesia.